Erectile Dysfunction: Clinical Guidelines (2) - Safarinejad, Mohammad Reza; Hosseini, Seyed Yousef (Urology Journal, 2009)
Purpose: According to a survey, the Massachusetts Male Aging Study, 52% of men beyond 40 years of age may have some degrees of erectile failure, and it is projected to affect 322 million men worldwide by 2025. We present a framework for the evaluation, treatment, and follow-up of the male patient who presents with erectile dysfunction. Materials and Methods: A comprehensive review of the literature was conducted using the MEDLINE database for all articles from 1975 through 2004 on male sexual dysfunction and the most pertinent articles are discussed. Results: Remarkable progress has been made in the treatment of erectile dysfunction (ED). Erectile dysfunction is a common condition associated with aging, chronic illnesses and various modifiable risk factors. Erectile dysfunction can be due to vasculogenic, neurogenic, hormonal, and/or psychogenic factors as well as alterations in the nitric oxide/cyclic guanosine monophosphate pathway or other regulatory mechanisms. The number of consultations from new patients presenting with erectile dysfunction and resulting costs for health care systems are increasing. Urologist should be the evaluating physician who supervises the surgical, medical, and hormonal treatment and who refers the patient, as necessary, to other members of the multidisciplinary team. Conclusion: Erectile dysfunction has a significant negative impact on quality of life. Male sexual dysfunction, especially erectile dysfunction, necessitates a comprehensive medical and psychologic evaluation involving both partners. All possible risk factors should be outlined and corrected, when feasible.